The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1210/jc.2008-1659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the rs997509 Polymorphism on the Association between Ectonucleotide Pyrophosphatase Phosphodiesterase 1 and Metabolic Syndrome and Impaired Glucose Tolerance in Childhood Obesity

Abstract: We conclude that the ENPP1 rs997509T allele can predispose obese children to MS and IGT and that this variant might drive the association between the ENPP1 121Q allele and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…Triglyceride, high-density lipoprotein (HDL) cholesterol, insulin, and glycemia levels were measured as previously described (27,28). Insulin resistance was assessed using the homeostasis model assessment (HOMA-IR), with a cut-off value of 3 (29).…”
Section: Patientsmentioning
confidence: 99%
“…Triglyceride, high-density lipoprotein (HDL) cholesterol, insulin, and glycemia levels were measured as previously described (27,28). Insulin resistance was assessed using the homeostasis model assessment (HOMA-IR), with a cut-off value of 3 (29).…”
Section: Patientsmentioning
confidence: 99%
“…[6][7][8][9] ENPP1 lies on chromosome 6q22-q23 (OMIM#173335) in a region where several independent studies found a linkage peak to OB phenotypes. [10][11][12][13] ENPP1 is an attractive candidate gene for studying OB, as it was proposed as a key player in the etiology of insulin resistance 14,15 and in a recently suggested mechanism underlying defective adipocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Santoro and cols. (63), studying lean and obese children, ob served that those who were carriers of the rs997509 T allele of ENPP1 gene presented higher levels of plasma insulin and HOMAIR (homeostasis model assessment -insulin resistance) and lower insulin sensitivity index compared with children who were homozygous for the most common allele. A similar observation was made for the Q variant of K121 polymorphism.…”
Section: Other Polymorphisms In Enpp1 Gene Associated With Diabetes Mmentioning
confidence: 99%
“…Besides, chil dren carrying the rare rs997509 T allele were at higher risk of developing metabolic syndrome and impaired glucose tolerance than children who were homozygous for the common allele. Evaluating the combined effects of polymorphisms rs997509 and K121Q, which are in strong disequilibrium linkage, the authors demonstra ted that the effect on insulin sensitivity was due to the presence of the rs997509 T allele and not due to the K121Q polymorphism (63).…”
Section: Other Polymorphisms In Enpp1 Gene Associated With Diabetes Mmentioning
confidence: 99%